Ośrodki i instytucie socjologii polskiej to pierwszych latach po drugiej wojnie światowej - Ruszczewska, Violetta (Wydział Prawa i Administracji UAM, 1990)
The author presents a fragment of the history of Polish sociology. She indicates that the sociological centres spread dynamically in the years following the emergence of a new socio-political system in Poland. The first sociological institution in the post-war period was the Polish Sociological Institute, opened in Lublin in 1944. Later the Institute was moved to Łódź The latter town may be considered a center of Polish sociology in the early post-war period also because many famous Polish sociologists (Chałasiński, Szczepański, Ossowski) carried out their scientific work there. Łódź was also the place where the only Polish sociological periodical of these years — „Przegląd Socjologiczny" (Sociological Review) — was published after Florian Znaniecki's emigration to the USA, Józef Chałasiński became the most distinguished Polish sociologist. Thanks to his scientific activity „Znaniecki school" was kept alive in Poland. Later, sociology found its place at the universities in Łódź, Lublin, Warsaw, Poznań and Wrocław. Besides, many other sociological institutions were established.
Centres and institutions of polish sociology in the early years after the second world war